2022
DOI: 10.59092/ijebi.vol1.iss1.8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Positive Psychological Capital on Social Entrepreneurship Intention During Covid-19

Abstract: The objective of this research is to identify the factor influencing sustainable entrepreneurial intention. This research uses a quantitative approach to examine the influence of psychological capital (hope, optimism, and resilience) and attitude on sustainable entrepreneurial intention. Survey of 156 Indonesian students was conducted to collect the data. The proposed hypothesis was tested with structural equation modelling. The result demonstrated that attitude and optimism have a positive  influence on  sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…The theory of hope suggests that people can achieve success by possessing cognitive abilities such as agency thinking and path thinking, which entail having the will to succeed and the perceived capacity to identify and pursue the path to success (Sedera et al, 2022;Rose, 2022). Alarcon et al (2013) found that hope is consistently associated with positive outcomes in areas such as academic and athletic performance, health, and psychological well-being.…”
Section: Hope and Task Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The theory of hope suggests that people can achieve success by possessing cognitive abilities such as agency thinking and path thinking, which entail having the will to succeed and the perceived capacity to identify and pursue the path to success (Sedera et al, 2022;Rose, 2022). Alarcon et al (2013) found that hope is consistently associated with positive outcomes in areas such as academic and athletic performance, health, and psychological well-being.…”
Section: Hope and Task Performancementioning
confidence: 99%
“…Hope and Work Engagement According to COR theory, resources are important inputs to work engagement, and hope is an important resource for generating both work engagement and task performance (Rose, 2022). High levels of Hope can lead to positive emotions, high expectations, and the belief that one has the necessary resources to succeed (Carton, 2018;Sedera et al, 2022). This, in turn, can promote engagement and motivation at work.…”
Section: Human Capital and Work Engagementmentioning
confidence: 99%